2020
DOI: 10.1103/physrevfluids.5.014803
|View full text |Cite
|
Sign up to set email alerts
|

Viscous reflection of internal waves from a slope

Abstract: Motivated by the laboratory experiments of Rodenborn et al. [Phys. Fluids 23, 026601 (2011)], a weakly nonlinear model is developed that accounts for viscous dissipation in the reflection of a finite-width internal wave beam from a uniform slope. Asymptotically, at high Reynolds number, viscous effects come into play predominantly in the immediate vicinity of the critical slope angle equal to the propagation angle to the horizontal of the incident wave beam. However, in the experiments of Rodenborn et al. whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The largest contribution is associated to the frequency ω 0 /N = 0.26, which comes from the incident and the reflected wave. As expected and already studied (Tabaei et al 2005;Rodenborn et al 2011;Kataoka and Akylas 2020), one can observe higher order frequencies (2ω 0 , 3ω 0 , etc.) with lower magnitude and a non vanishing contribution to the signal at ω/N = 0.…”
Section: Temporal Filteringsupporting
confidence: 86%
“…The largest contribution is associated to the frequency ω 0 /N = 0.26, which comes from the incident and the reflected wave. As expected and already studied (Tabaei et al 2005;Rodenborn et al 2011;Kataoka and Akylas 2020), one can observe higher order frequencies (2ω 0 , 3ω 0 , etc.) with lower magnitude and a non vanishing contribution to the signal at ω/N = 0.…”
Section: Temporal Filteringsupporting
confidence: 86%
“…Chalamalla et al (2013) reported that the turbulent kinetic energy can be higher for somewhat off-critical reflection compared to exactly critical reflection under certain conditions. A weakly nonlinear model (Kataoka & Akylas 2020) also shows that in some conditions, the viscous effect can be important during the wave reflection from a slope, which leads to the deviation of the optimal off-criticality from zero.…”
Section: Profiles Of Dissipation Rate and Kinetic Energymentioning
confidence: 99%
“…Furthermore, similar to in (4.1), the forcing amplitude parameter in (4.2) is chosen such that the integral in the central vertical plane () of the numerically computed mean-flow velocity in the direction at 20 beam periods matches the value of this integral based on the experimental mean-flow data at the same time. The Navier–Stokes equations are solved numerically by adapting to the present three-dimensional geometry the procedure outlined in Kataoka & Akylas (2020) for two-dimensional reflection of an internal wave beam from a rigid slope. The results reported here were obtained using the computational domain with grid points and the time step s. The grid points were more concentrated near the wave generator in order to achieve higher resolution there.…”
Section: Comparison Of Theory With Experimentsmentioning
confidence: 99%